COMPARATIVE STUDY OF THE CLINICAL OUTCOMES OF DIFFERENT TECHNIQUES FOR THE MANAGEMENT OF FACIAL TRAUMA (Journal of Medical & Health Sciences Review, 2025)
Background: Facial trauma presents a significant clinical challenge due to its impact on both functional and aesthetic outcomes. Various surgical techniques, including Open Reduction and Internal Fixation (ORIF), minimally invasive fixation, and conservative management, are employed to optimize recovery. However, comparative evidence on their efficacy remains limited.Objective: This study aims to evaluate and compare the clinical outcomes, complication rates, functional recovery, and hospital stay durations associated with different surgical techniques for managing facial fractures.Methods:  A retrospective cohort study was conducted using medical records of 350 patients treated for facial trauma at multiple tertiary care hospitals. Patients were categorized based on treatment modality: ORIF (n=195), minimally invasive fixation (n=106), and conservative management (n=49). Primary outcome measures included postoperative complications, functional recovery (jaw mobility and occlusion), and aesthetic outcomes. Secondary outcomes included hospital stay duration and time to resume normal activities. Statistical analyses, including chi-square tests and ANOVA, were performed to compare treatment efficacy.Results: ORIF demonstrated the highest success rates, with 86.2% of patients achieving normal jaw function within 8 weeks and 92.8% reporting satisfactory aesthetic outcomes. Minimally invasive fixation yielded comparable results, with shorter hospital stays (mean: 3.5 days) and faster return to normal activities (mean: 4.2 weeks). Conservative management resulted in prolonged recovery and higher rates of malocclusion (10.2%). Postoperative complications were highest in ORIF cases (18.6%), though statistically significant differences were noted between groups (p < 0.05).Conclusion: ORIF remains the preferred method for complex facial fractures due to superior functional and aesthetic outcomes. Minimally invasive techniques offer an effective alternative with faster recovery and reduced hospital stays, making them suitable for selected cases. Conservative management demonstrated higher complication rates and delayed functional recovery, limiting its applicability. Future studies should focus on long-term outcomes and patient-reported satisfaction to refine surgical decision-making.